Challenge. Vol. 3, no. 11 - Gollan, John ; Moran, Jim ; Hughes, A. R. ; Gillan, Phil ; McCulloch, Molly ; Thomas, Bert; Garber, Joe (London : Challenge Publications)
1937-03-11 SA15-003-001 8 pages : illustrations ; 30 cm. 15X/1/34/1